Investigating English Vocabulary Difficulties and Its Learning Strategies of Lower Secondary School Students - Amrina Rosyada-AS; Tri Wintolo Apoko (Universitas Pendidikan Mandalika, 2023)
Vocabulary plays a crucial role in language proficiency as it serves as the foundation for effective language acquisition. The ability to acquire vocabulary is considered a prerequisite for learning a language. Therefore, the primary objective of this research is to investigate the difficulties encountered by students in their vocabulary learning process as well as the strategies they employ to overcome these obstacles in the context of English vocabulary acquisition. The participants in this study consisted of nine students at various proficiency levels in a lower secondary school, along with one English teacher. Employing a descriptive qualitative method, semi-structured interviews were conducted to gather data for this research. The interview questions focused on investigating the difficulties students faced in learning English vocabulary and the strategies they utilized to address these challenges. To facilitate data analysis, each interview was meticulously recorded and transcribed. The data analysis technique employed in this research entailed descriptive analysis. The findings of this study revealed that a significant number of students encountered difficulties in acquiring vocabulary. Specifically, these challenges manifested in areas such as the correct pronunciation of new words, accurate spelling, proper usage of word meanings, and effective retention or memorization of vocabulary. In order to mitigate these difficulties, students employed various strategies, including utilizing media resources such as smartphones, the internet, and games as well as employing note-taking techniques and consulting dictionaries to aid their vocabulary learning process.